2015
DOI: 10.1089/scd.2014.0546
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem/Progenitor Cells Express Several Functional Sex Hormone Receptors—Novel Evidence for a Potential Developmental Link Between Hematopoiesis and Primordial Germ Cells

Abstract: Evidence has accumulated that hematopoietic stem progenitor cells (HSPCs) share several markers with the germline, a connection supported by reports that prolactin, androgens, and estrogens stimulate hematopoiesis. To address this issue more directly, we tested the expression of receptors for pituitary-derived hormones, such as follicle-stimulating hormone (FSH) and luteinizing hormone (LH), on purified murine bone marrow (BM) cells enriched for HSPCs and tested the functionality of these receptors in ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 46 publications
(83 reference statements)
8
90
0
Order By: Relevance
“…Namely, since pituitary SexH receptors are expressed by cells from the germ lineage beginning at the very early stages of embryogenesis (35,36), and, as demonstrated in this study, lung cancer cells also express pituitary SexH rec eptors, there may be a developmental link between these cells, as suggested at the beginning of this section. Interestingly, 150 years ago Virchow (37) and Cohnheim (38) proposed that some malignancies develop from dormant embryonic or germ cells residing in adult tissues.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Namely, since pituitary SexH receptors are expressed by cells from the germ lineage beginning at the very early stages of embryogenesis (35,36), and, as demonstrated in this study, lung cancer cells also express pituitary SexH rec eptors, there may be a developmental link between these cells, as suggested at the beginning of this section. Interestingly, 150 years ago Virchow (37) and Cohnheim (38) proposed that some malignancies develop from dormant embryonic or germ cells residing in adult tissues.…”
Section: Discussionsupporting
confidence: 60%
“…One can speculate that these or closely related cells could theoretically be the source of some tumors. In support of this possibility, VSELs express several SexH receptors as well as genes involved in primordial germ cell development (35,36,39,41). This working hypothesis, however, requires more experimental evidence.…”
Section: Discussionmentioning
confidence: 89%
“…2e,f). Although Lhcgr expression has previously been demonstrated in a crude fraction of Lin − CD45 + Sca1 + cells 3 , this is the first evidence to our knowledge of its enriched expression in the most primitive HSCs.…”
mentioning
confidence: 54%
“…In addition to their role in promoting sexual dimorphisms, increasing evidence suggests that sex hormones regulate HSC self-renewal, differentiation, and proliferation 35 . We and others previously reported that sex steroid ablation promotes bone marrow (BM) lymphopoiesis and HSC recovery in aged and immunodepleted mice 57 .…”
mentioning
confidence: 99%
“…However, data have shown that leuprolide acetate, a luteinizing hormone-releasing hormone agonist increases the myeloid progenitor cells in the bone marrow [38]. The first studies on LH and hematopoietic stem/progenitor cell found that hematopoietic stem/progenitor cell express functional FSH and LH receptors that proliferate in vivo and in vitro in response to FSH and LH [39]. Abdelbaset-Ismail and colleagues further affirmed that LH stimulates growth of human hematopoietic/ progenitor cells and mesenchymal cells in vivo and in vitro [40].…”
Section: Evaluation Of the Effects Of Tetrapleura Tetraptera Extract mentioning
confidence: 99%